EPS3.02A preferential orientation adipocyte differentiation of CFTR-mutated mesenchymal stem cells: predisposing factor to cystic fibrosis-related bone diseases - Hamon, L.; Dumortier, C.; Thoraval, L.; Sergheraert, J.; Piot, O.; Buache, E.; Goffin, N.; Chauveau, C.; Gangloff, S.; Alam, D. Al; Jourdain, M.-L.; Velard, F. (Journal of cystic fibrosis, 2025)
Cystic Fibrosis-related Bone Disease (CFBD) affects 50% of CF adult patients. Osteoblasts obtained from CF induced pluripotent stem cells (iPSCs) evidenced a higher PPARG level (adipocyte transcription factor) than healthy control line. In several pathologies, a relationship exists between low bone density and increased medullar adiposity. We hypothesized that there is a preferential adipocyte differentiation triggered in mesenchymal stem cells (MSC) bearing mutation in CFTR gene. MSC from healthy donors have been differentiated into adipocytes and osteoblasts during 21 days, with or without Inh172 or BPO27 (CFTR pharmacological inhibitors) (n=7). Oil Red'O, BodipyTM, FABP4 and PPARG (adipocytes specific proteins) stainings were performed. Raman microspectroscopy was used to determine the nature of lipid content. MicroCT analysis of WT and F508delCFTR 24-week-old mice have who had surgical ovariectomy (OVX) or not was performed to assess bone microarchitecture. Blocking CFTR has a direct effect on the increase of adipocytes number and lipid vesicles size (p<0.05). Raman analyses showed an increased saturation degree of lipids. Spontaneous lipid droplets generation was evidenced in MSC and osteoblasts with CFTR inhibitors. In vivo, data showed a decreased trabecular thickness in CF versus WT mice, leading to the alteration of bone microarchitecture. We highlight a trend towards a decrease in bone mineral density in OVX-CF mice. In addition, the number of bone trabeculae decreased contrary to the trabecular separation that increased in OVX-CF mice, compared to CF mice. These data may reflect MSC commitment towards adipocyte lineage due to a loss of CFTR function. More, we evidenced a more pronounced manifestation of CFBD in OVX mice, thus highlighting the potential impact of post-menauposis on female CF patients. Finally, understanding the formation and role of lipid metabolism in this context may be a promising avenue to better understand and cure CFBD.